Recyclable magnetic catalyst as well as preparation method and application thereof

By loading the recyclable magnetic catalysts formed by iron trioxide and magnesium oxide nanoparticles on sepiolite, the problems of low reuse rate and low free radical utilization rate are solved, and the efficient catalytic degradation of difficult-to-degradable organic matter in printing and dyeing wastewater are achieved, and long life and efficient decolorization are provided.

CN120361895APending Publication Date: 2025-07-25WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510452387.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-11
Publication Date
2025-07-25

AI Technical Summary

Technical Problem

When treating printing and dyeing wastewater, existing catalysts have problems such as easy loss of metal ions, low catalyst reuse rate, high cost, and low radical utilization rate, and traditional ozone oxidation technology is low in efficiency and poor selectivity.

Method used

Sepiolite is used as a support and is loaded with iron tetraoxide particles and magnesium oxide nanoparticles to form a recyclable magnetic catalyst, and ozone is generated through an ozone generator for catalytic degradation. The adsorption-catalytic synergy of magnetic catalysts are used to improve the utilization rate of free radicals and catalytic performance.

Benefits of technology

It realizes efficient recycling and utilization of catalysts, improves the utilization rate and catalytic efficiency of free radicals, degrades difficult-to-degradable organic matter in printing and dyeing wastewater, has long life and efficient decolorization capabilities, and is suitable for high-concentration organic wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120361895A_ABST
    Figure CN120361895A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of research and development of catalysts for sewage treatment, in particular to a recoverable magnetic catalyst as well as a preparation method and application thereof, and the catalyst comprises fibrous sepiolite, ferroferric oxide particles and magnesium oxide nanoparticles, and the ferroferric oxide particles and the magnesium oxide nanoparticles are loaded on the sepiolite. According to the method, meerschaum is mainly used as a carrier as a main adsorption material, and metal oxide is loaded on the surface and in a pore structure of the fibrous meerschaum as a catalytic part. The catalyst material prepared by the method is uniform in element distribution, multiple in active sites, excellent in catalytic performance, easy to recycle, stable in structure and capable of being recycled, and has a huge application value in the field of purification of printing and dyeing wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalyst research and development for sewage treatment, and particularly relates to a recyclable magnetic catalyst, a preparation method thereof, and an application thereof. Background Art

[0002] With the continuous development of the dye industry in China and the invention and application of various new dyes, the discharge of wastewater from the textile dyeing and finishing industry in China has increased significantly, becoming one of the wastewaters with a large discharge. Printing and dyeing wastewater also has poor biodegradability, complex composition, high chroma and salt content, and has a certain biological toxicity, greatly increasing the difficulty of its degradation. Among them, dyes such as reactive yellow are widely used in the printing and dyeing field. Due to its significant chemical properties, its molecules contain reactive groups. Common reactive groups include vinyl chloride group, sulfate group, aminomethyl group, etc. These groups can undergo covalent reactions with the groups on the fiber surface to form a firm bond. However, the unreacted dyes and salt substances contained in reactive dyes may cause environmental pollution, and the organic matter concentration is high and it is difficult to biodegrade, which is also a difficult problem in the treatment of dye wastewater at present.

[0003] Advanced oxidation processes are effective methods proven to degrade chemical industrial wastewater at present. Commonly used ones include photocatalytic method, electrocatalytic method, Fenton oxidation method, persulfate oxidation method, etc. The photocatalytic method only has a good degradation effect on pollutants with good photosensitivity, and the degradation time is long; the degradation of pollutants by the electrocatalytic method is restricted by many factors such as electrolytes, electrode materials, operating conditions, and pollutant concentration, and the electrodes are also corroded; Fenton oxidation depends on the catalytic activity of metals. This method has a good pollutant removal rate, but the process is slow and the reaction conditions are extremely harsh; the persulfate method has harsh reaction conditions, the oxidation process requires a high temperature and a long reaction time, the reaction selectivity is poor, and a large amount of sulfate radicals will be generated. How to remove sulfur is a technical difficulty at present. At present, ozone oxidation has gradually developed into a catalytic ozonation technology system. By using a catalyst, ozone is significantly enhanced to generate active free radicals on the catalyst surface, so as to achieve a more rapid and efficient degradation ability. Moreover, the generated free radicals have no selectivity for pollutant types, greatly overcoming the disadvantages of small ozone solubility, weak stability, low utilization rate, and poor mass transfer efficiency in the traditional ozone oxidation technology.

[0004] With the continuous development of the catalytic ozonation technology, many representative catalysts have been developed at present, mainly including the research of homogeneous catalysts and heterogeneous catalysts. However, the active ingredient metal ions of the commonly used homogeneous catalysts are easy to lose, causing secondary pollution, and it is difficult to effectively separate from clean water, resulting in an increase in cost. At the same time, the specific surface area of metal oxides in heterogeneous catalysts is limited, the surface active sites are insufficient, and some catalysts are easy to break and lose, resulting in low catalyst reuse rate. There are also problems such as high costs for separation and recovery methods such as centrifugation and filtration. Summary of the Invention

[0005] Aiming at the deficiencies existing in the prior art, the present invention innovatively develops a recyclable magnetic catalyst, its preparation method and application. This method mainly uses sepiolite as the carrier as the main adsorption material, and at the same time loads metal oxides on the surface and pore structure of fibrous sepiolite as the catalytic part. The catalyst material prepared by this method has uniform element distribution, many active sites, excellent catalytic performance, easy recycling, and the catalyst structure is stable and can be recycled, showing great application value in the field of purifying printing and dyeing wastewater.

[0006] To achieve the above object, the present invention is realized through the following technical solutions:

[0007] In the first aspect, the present invention provides a recyclable magnetic catalyst, including fibrous sepiolite and magnetite particles and magnesium oxide nanoparticles loaded on the sepiolite.

[0008] As a further optimized scheme of the present invention, the particle size of the magnetite particles is 1-5 μm, and the particle size of the magnesium oxide nanoparticles is 10-50 nm.

[0009] In the second aspect, the present invention provides a preparation method of the recyclable magnetic catalyst, including the following steps:

[0010] (1) Prepare magnetite particles;

[0011] (2) Disperse and dissolve sepiolite in water to form solution C, dissolve magnetite particles in water to form particle colloidal suspension D, slowly drip colloidal suspension D into solution C, stir evenly to obtain solution E, then dissolve magnesium chloride hexahydrate in water to prepare solution F, add solution F to solution E, heat and stir to obtain solution G, drip sodium hydroxide solution B into solution G and stir, the obtained solution is centrifuged, washed with alcohol, washed with water, dried, the dried compound is calcined, and finally the obtained compound is ground and sieved to obtain the recyclable magnetic catalyst.

[0012] The reaction mechanism of step (2) is:

[0013] Dispersion of the carrier and loading of Fe3O4:

[0014] Sepiolite (Sep) forms a stable suspension after ultrasonic dispersion. Its fibrous structure surface is rich in hydroxyl groups (—OH), which can combine with Fe3O4 particles through physical adsorption or electrostatic interaction. The Fe3O4 colloidal suspension is dropped into the sepiolite solution, and during the stirring process, the Fe3O4 particles are embedded in the pores of the sepiolite fibers or attached to the surface.

[0015] Formation and loading of magnesium oxide (MgO):

[0016] After magnesium chloride hexahydrate (MgCl₂·6H₂O) is dissolved, magnesium hydroxide precipitate is formed by hydrolysis under alkaline conditions (pH = 8 - 10):

[0017] Mg 2+ + 2OH - → Mg(OH)₂

[0018] Heating (70 - 90 °C) promotes the dehydration of Mg(OH)₂ and it is converted to MgO by calcination (400 - 550 °C):

[0019] Mg(OH)₂ → MgO + H₂O

[0020] Construction of composite structure:

[0021] Fe₃O₄ provides magnetism for subsequent recovery; MgO serves as a catalytic active site and synergistically acts with the adsorption capacity of sepiolite to enhance pollutant enrichment and free radical utilization rate. The calcination process further solidifies the carrier and the active components, improving the thermal stability and structural strength of the material.

[0022] As a further optimized scheme of the present invention, the method for preparing the iron oxide particles in step (1) includes: dissolving ferric chloride hexahydrate and ferrous sulfate heptahydrate in an ethylene glycol aqueous solution to prepare solution A, dropping sodium hydroxide aqueous solution B into solution A and stirring, and then cooling, washing, drying and grinding.

[0023] The reaction mechanism of step (1) is as follows:

[0024] Dissolution and reduction of raw materials:

[0025] Ferric chloride hexahydrate (FeCl₃·6H₂O) and ferrous sulfate heptahydrate (FeSO₄·7H₂O) are dissolved in an ethylene glycol / water solution. Ethylene glycol serves both as a solvent and as a weak reducing agent and stabilizer.

[0026] Fe 3+ and Fe 2+ The mixed solution undergoes a coprecipitation reaction under alkaline conditions (pH = 8 - 10). Ethylene glycol slows down the hydrolysis rate of iron ions through complexation and controls the nucleation and growth of particles.

[0027] Coprecipitation and crystallization:

[0028] After adding sodium hydroxide (NaOH), OH - combines with Fe 3+ and Fe 2+ to form the crystal nucleus of Fe₃O₄:

[0029] Fe 3+ + 2Fe 2+ + 8OH -→Fe3O4 + 4H2O

[0030] Long - time stirring (10 - 14 hours) promotes the homogenization of crystal growth and reduces agglomeration.

[0031] Post - treatment:

[0032] After cooling, repeatedly wash to remove residual ions, dry and grind to obtain Fe3O4 particles with good dispersibility.

[0033] As a further optimization scheme of the present invention, in step (1), an aqueous sodium hydroxide solution B is dropped into solution A, the pH is adjusted to 8 - 10, and the stirring time is 10 - 14 h. The alkaline environment is a necessary condition for the formation of Fe3O4 and affects the particle dispersibility at the same time.

[0034] As a further optimization scheme of the present invention, in step (2), the mass ratio of sepiolite, iron tetroxide particles and magnesium chloride hexahydrate is (1 - 1.5):(1.5 - 2.5):(4 - 6). This ratio optimizes the distribution of active sites and the carrier loading capacity.

[0035] As a further optimization scheme of the present invention, in step (2), the heating and stirring conditions are: heating to 70 - 90 °C and maintaining a constant temperature for stirring for 0.5 - 1 h.

[0036] As a further optimization scheme of the present invention, in step (2), the calcination conditions are: the calcination temperature in a muffle furnace is 400 - 550 °C, and the calcination time is 4 - 6 h. Heating promotes the conversion of Mg(OH)2 to MgO, and calcination eliminates organic matter residues and enhances crystallinity.

[0037] As a further optimization scheme of the present invention, in step (2), an aqueous sodium hydroxide solution B is dropped into solution G and stirred, the pH is adjusted to 8 - 10, and the stirring time is 0.5 - 1 h. The alkaline environment is a necessary condition for the formation of MgO and affects the particle dispersibility at the same time.

[0038] In the third aspect, the present invention provides an application of the recyclable magnetic catalyst described above in treating printing and dyeing wastewater.

[0039] As a further optimization scheme of the present invention, the application method includes: adding the catalyst material to the printing and dyeing wastewater, generating ozone by an ozone generator and introducing it into the reactor to degrade the refractory organic matter molecules in the printing and dyeing wastewater.

[0040] As a further optimization scheme of the present invention, the dye wastewater is a weakly alkaline system, the dosage of the magnetic composite catalyst material is 0.5 - 2.5 g / L, and the ozone concentration is 30 - 70 mg / L.

[0041] As a further optimized solution of the present invention, the catalyst material after the reaction is simply washed twice with deionized water, and then statically separated by applying an external magnetic field in a beaker. The separated catalyst is dried in an oven, and the dried magnetic catalyst can be recycled.

[0042] Compared with the prior art, the beneficial effects achieved by the present invention are as follows:

[0043] 1. At present, the cost of centrifuging and filtering and recycling many traditional ozone catalyst materials is relatively high, and there is a large loss during the catalyst recycling process. The magnetic catalyst material prepared by the present invention can be recycled by simply applying an external magnetic field, which is more economical and environmentally friendly.

[0044] 2. At present, the free radical utilization rate of traditional metal catalyst materials is relatively low. The possible reason is that the catalyst materials do not have or have very little adsorption, so that the pollutant molecules cannot fully contact with the catalyst materials. Moreover, the generation and degradation of free radicals are both completed on the surface of the catalyst, and at the same time, the free radical lifetime is extremely short, resulting in a large amount of free radical waste. The magnetic catalyst material prepared by the present invention has the synergistic effect of two functions of adsorption and catalysis, greatly improving the free radical utilization rate and enhancing the oxidation ability and reaction rate of ozone.

[0045] 3. The catalyst prepared in the present invention has the advantages of long life and fast decolorization. Its main active site lies in the loaded magnesium oxide. The catalyst can be recycled for a long time. It only needs simple magnetic recovery to continue to be used, and it has good catalytic effect. It can still achieve almost complete decolorization for high-concentration organic wastewater.

[0046] 4. The preparation method described in the present invention has simple process, simple and easily available materials, low cost, and meets environmental requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 It is the SEM pattern of MgO@Fe3O4@Sep prepared in Example 1 of the present invention.

[0048] Figure 2 It is the EDS pattern of MgO@Fe3O4@Sep prepared in Example 1 of the present invention.

[0049] Figure 3 It is the XRD pattern of MgO@Fe3O4@Sep prepared in Example 1 of the present invention.

[0050] Figure 4 It is the BET pattern of different materials in Example 6 of the present invention; wherein Figure a is the BET pattern of Fe3O4; Figure b is the BET pattern of MgO@Fe3O4@Sep.

[0051] Figure 5This is the influence of different catalyst concentrations on the dye degradation rate in Example 7 of the present invention.

[0052] Figure 6 This is the influence of different ozone concentrations on the dye degradation rate in Example 8 of the present invention.

[0053] Figure 7 This is the influence of different pH values on the dye degradation rate in Example 9 of the present invention.

[0054] Figure 8 This is the recycling performance of the recyclable magnetic catalyst in Example 10 of the present invention.

[0055] Figure 9 This is the evaluation of the adsorption and catalytic performance of different catalysts in Example 11 of the present invention.

[0056] Figure 10 This is the evaluation of the actual wastewater degradation effect of the recyclable magnetic catalyst in Application Example 1 of the present invention. Detailed implementation manners

[0057] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the preferred implementation manners of the present invention will be described below in conjunction with specific embodiments. However, it should not be construed as a limitation of the present invention, and only for example.

[0058] Example 1 A preparation method of a recyclable magnetic catalyst MgO@Fe3O4@Sep:

[0059] Fe3O4 particles were synthesized by an eco-friendly precipitation method. Weigh 2.334 g of ferric chloride hexahydrate (FeCl3·6H2O, 99%) and 1.20 g of ferrous sulfate heptahydrate (FeSO4·7H2O, 99%) and dissolve them in 100 mL of ethylene glycol / deionized water (1:1) solution. Dissolve for 30 min at room temperature of 25°C under nitrogen conditions, then add 1 mol / L of sodium hydroxide (NaOH), stir vigorously and adjust to pH = 9. Next, continue to stir the solution vigorously for 12 hours. Finally, cool the mixture to room temperature, wash it several times with ultrapure water, and dry it overnight at 70°C. After drying, grind it.

[0060] The synthesized Fe3O4 was mixed with magnesium chloride hexahydrate and sepiolite raw material (Sep) by heterogeneous suspension method. 1 g of sepiolite (Sep, 99%) powder was ultrasonically dispersed in 100 mL of deionized water for 1 h, then 200 mL of Fe3O4 particle colloidal suspension (10 mg / mL) was slowly dropped into the Sep solution, and vigorously stirred for 3 h. Subsequently, 100 mL of pre-prepared magnesium chloride hexahydrate solution (50 mg / mL, MgCl2·6H2O, 99%) was added, the electromagnetic stirring mixing temperature was raised to 85 °C, and stirring was continued for 30 min. Then, 1 mol / L sodium hydroxide (NaOH) solution was slowly added until the pH reached 9, and mixed for 1 h. Finally, the obtained solution was centrifuged, and washed twice with ethanol and pure water respectively. The synthesized compound was dried at 105 °C for 24 h, then calcined in a furnace at 450 °C for 5 h, and ground in a mortar after calcination.

[0061] The adsorption capacity experiment was carried out on the recyclable magnetic catalyst prepared according to the above method. The adsorption capacity of the prepared catalyst MgO@Fe3O4@Sep was 173.65 mg / g, while the adsorption capacity of Fe3O4 was 89.15 mg / g.

[0062] Example 2 A preparation method of a recyclable magnetic catalyst MgO@Fe3O4@Sep:

[0063] The preparation method was the same as that of Example 1. The difference in the synthesis of Fe3O4 particles was that sodium hydroxide was added to adjust the pH to 8, and stirring was continued for 10 hours. The difference in the loading method was that the mass ratio of sepiolite, iron tetroxide and magnesium chloride hexahydrate in the raw material dosage was 1.5:2.5:6, the electromagnetic stirring temperature of the solution was 70 °C, the heating and stirring time was 0.5 h, sodium hydroxide was added until the pH was 8, the stirring time was 1 h, the calcination temperature was 400 °C, and the calcination time was 4 h.

[0064] The adsorption capacity experiment was carried out on the recyclable magnetic catalyst prepared according to the above method. The adsorption capacity of the prepared catalyst MgO@Fe3O4@Sep was 168.77 mg / g, while the adsorption capacity of Fe3O4 was 86.36 mg / g, and the material properties of the catalyst synthesized in Example 1 were very little different.

[0065] Example 3 A preparation method of a recyclable magnetic catalyst MgO@Fe3O4@Sep:

[0066] The preparation method is the same as that of Example 1. The difference in synthesizing Fe3O4 particles lies in that sodium hydroxide is added to adjust the pH to 10, and stirring is continued for 14 hours. The difference in the loading method lies in that the mass ratio of sepiolite, iron tetroxide, and magnesium chloride hexahydrate in the raw material dosage is 1:1.5:4, the temperature of electromagnetic stirring of the solution is 90 °C, the heating and stirring time is 1 h, sodium hydroxide is added until the pH is 10, the stirring time is 1 h, the calcination temperature is 550 °C, and the calcination time is 6 h.

[0067] The adsorption capacity experiment was carried out on the recoverable magnetic catalyst prepared according to the above method. The adsorption capacity of the prepared catalyst MgO@Fe3O4@Sep was 166.84 mg / g, while the adsorption capacity of Fe3O4 was 85.28 mg / g, and the material properties of the catalyst synthesized in Example 1 had very little difference.

[0068] Example 4 A preparation method of a recoverable magnetic catalyst MgO@Fe3O4@Sep:

[0069] The preparation method is the same as that of Example 1. The difference in the loading method lies in that the mass ratio of sepiolite, iron tetroxide, and magnesium chloride hexahydrate in the raw material dosage is 1.5:2:6, the temperature of electromagnetic stirring of the solution is 80 °C, the heating and stirring time is 0.5 h, the stirring time after adding sodium hydroxide is 1 h, the calcination temperature is 500 °C, and the calcination time is 5 h.

[0070] The adsorption capacity experiment was carried out on the recoverable magnetic catalyst prepared according to the above method. The adsorption capacity of the prepared catalyst MgO@Fe3O4@Sep was 166.79 mg / g, while the adsorption capacity of Fe3O4 was 86.05 mg / g, and the material properties of the catalyst synthesized in Example 1 had very little difference.

[0071] Example 5 Structure of the recoverable magnetic catalyst material:

[0072] From Figure 1 a and b in it, it can be seen that the original structure of sepiolite is composed of many fine bundle-like fibers, and the fibrous fibrils are intertwined randomly and the surface is smooth. From Figure 1 c and d in it, it can be seen that after the iron-magnesium modification treatment, we can see a large number of spherical substances randomly distributed on the surface and in the gaps of the sepiolite fiber structure. Moreover, in addition to the larger spherical particles, there are many small synaptic-like substances on the surface of the spherical particles and the surface of sepiolite. This indicates that Fe3O4 particles and MgO nanoparticles are incorporated into the original sepiolite. The Fe3O4 particles are composed of a large number of Fe3O4 crystals, with a loose structure and a dispersed spherical shape, while the MgO nanoparticles have a cubic crystal structure and are in the shape of irregular rods or spheres, that is, the small synaptic-like substances in the material. This proves that the metal oxides are successfully loaded on the surface and in the internal pores of sepiolite. See the element mapping diagram of the recoverable magnetic catalyst material inFigure 2 It can be seen that the Fe element is evenly loaded on the catalyst.

[0073] The X-ray diffraction pattern of the recyclable magnetic catalyst material is shown in Figure 3 . It can be seen from the figure that the characteristic diffraction peaks of MgO and Fe3O4 can be found, indicating that the two substances are successfully crystallized and loaded on the surface of sepiolite, and no additional peaks of other phases are detected except for the sepiolite component, indicating that no chemical reaction occurs between the components during our synthesis process and no other metal oxide components are introduced on the material surface.

[0074] Pore structure and specific surface area of the recyclable magnetic catalyst material in Example 6:

[0075] From Figure 4 , it can be seen that both Fe3O4 and MgO@Fe3O4@Sep form a closed H2b-type hysteresis loop, proving that both have a stable mesoporous structure. By comparison, the isothermal hysteresis loop of MgO@Fe3O4@Sep is wider than that of pure Fe3O4, which proves that its pore structure is larger. The reason for the analysis is that the introduction of sepiolite changes the pore structure, increases the pore size, and the pores are not agglomerated and blocked during the material synthesis process, so the pore structure becomes larger. The pore analysis results show that the specific surface areas of Fe3O4 and MgO@Fe3O4@Sep are 59.8 m 2 / g and 64.2 m 2 / g, the pore volumes are 0.22 cm 3 / g and 0.29 cm 3 / g, and the pore diameters are 14.7 nm and 20.0 nm respectively. As a mineral material with a porous structure, the high specific surface area of sepiolite can greatly enhance the adsorption performance of the material ( Figure 9 ), because the crystal structure of sepiolite itself consists of two layers of silicon-oxygen tetrahedrons sandwiching one layer of magnesium-oxygen octahedrons, forming a unique 2:1 type layer-chain structure with a very high specific surface area. When we prepare the catalyst by the heterogeneous suspension method, the network structure of sepiolite fibers can effectively prevent the agglomeration of MgO and Fe3O4.

[0076] Effect of catalyst concentration on the catalytic ozonation performance of the recyclable magnetic catalyst in Example 7:

[0077] Weigh 0.1, 0.2, 0.3, 0.4, and 0.5 g of MgO@Fe3O4@Sep prepared in Example 1 respectively, add them to 200 mL of dye wastewater with a concentration of 1000 mg / L prepared with reactive yellow, and carry out degradation under the condition of an ozone concentration of 50 mg / L for 60 min. Take out 5 mL of the sample solution every 20 min to measure its absorbance, and calculate the dye degradation rate according to formula (1).

[0078]

[0079] Among them, η is the pollutant degradation rate (%); C0 is the pollutant concentration (mg / L); C t is the remaining concentration (mg / L) of the pollutant at time t (min).

[0080] The results are as Figure 5 shown. We can see that as the catalyst concentration increases, the degradation rate and degradation effect at each time point increase continuously. With the increase of the catalyst concentration, more active sites are exposed by the catalyst, which improves the contact probability between substances and molecules in the heterogeneous system. The increase in the contact between the pollutant and the catalyst makes the utilization rate of ·OH generated on the catalyst surface by ozone higher, avoiding the waste caused by the short lifespan. When the catalyst concentration is 2.5 g / L, the degradation rate can reach 94.8% at 20 min and 99.6% at 40 min.

[0081] Example 8: Influence of ozone concentration on the catalytic ozonation performance of the recyclable magnetic catalyst

[0082] Weigh 0.2 g of MgO@Fe3O4@Sep prepared in Example 1 and add it to 200 mL of dye wastewater with an active yellow concentration of 1000 mg / L. Degradation is carried out under the conditions of ozone concentrations of 30, 40, 50, 60, and 70 mg / L for 60 min. Take out 5 mL of the sample solution every 20 min to measure its absorbance, and calculate the dye degradation rate according to formula (1). The results are as Figure 6 shown. We can see that when the ozone concentration increases, the concentration difference at the gas-liquid interface increases, and the mass transfer rate increases under the drive of the concentration difference, resulting in an increase in the solubility of ozone. Therefore, more ozone molecules contact the catalyst, but it can also be seen that there is a maximum solubility of ozone. When we continue to increase the ozone concentration, the effect decreases instead. When the ozone concentration is 50 mg / L, the degradation effect is the best, reaching a degradation rate of 83.6% at 20 min and 98.3% at 40 min.

[0083] Example 9: Influence of pH on the catalytic ozonation performance of the recyclable magnetic catalyst

[0084] Weigh 0.2 g of MgO@Fe3O4@Sep prepared in Example 1 and add it to 200 mL of dye wastewater with an active yellow concentration of 1000 mg / L. Adjust the pH to 3 - 11 respectively, and carry out degradation under the condition of an ozone concentration of 40 mg / L for 60 min. Take out 5 mL of the sample solution every 20 min to measure its absorbance, and calculate the dye degradation rate according to formula (1). The results are as Figure 7As shown, we can see that within the pH range of 3 - 11, the degradation effect of the catalyst varies little, proving that the influence of pH on catalytic degradation is small. Therefore, in practical applications, it can adapt to actual wastewater with various pH values for degradation. Under the condition of pH = 8, the degradation rate can reach 81.2% at 20 min and 95.02% at 40 min.

[0085] Recycling performance of the recoverable magnetic catalyst in Example 10:

[0086] Weigh 0.2 g of MgO@Fe3O4@Sep prepared in Example 1 and add it to 200 mL of dye wastewater with a concentration of 1000 mg / L prepared from reactive yellow. Adjust the pH to 8 and carry out degradation under the condition of an ozone concentration of 40 mg / L. React for 60 min, take out 5 mL of the sample solution every 20 min to measure its absorbance, and calculate the dye degradation rate according to formula (1). The results are as Figure 8 shown. We can see that after five recycles, the decolorization rate of the reactive yellow dye does not decrease significantly, proving that the recycling effect is good. The specific losses are shown in Table 1 below. The recycling method we adopted is simple magnetic recycling. Use a magnet to stick to the bottom of the beaker until the catalyst settles completely, pour out the excess liquid, and then wash it with water and alcohol and dry it. The recycling cost is low, simple and convenient, and the effect is excellent, suitable for practical applications. The loss for each recycle is about 7.4 - 9.8%. Since the amount of the catalyst we used is only 0.2 g, a certain amount will be fixed and lost during the cleaning and recycling process, so the recycling efficiency decreases. When the dosage is increased and applied in actual use, it will be much less than this loss. In addition, we also carried out supplementary experiments. Weigh out 0.2 g of the catalyst recovered each time separately and conduct experiments under the same other conditions. The results show that the dye degradation rate in five cycles remains almost unchanged. This indicates that the active components of the catalyst are firmly combined with the carrier, not easily falling off, and have a long service life, but there are still certain losses during the magnetic recycling process.

[0087] Evaluation of the adsorption and catalytic efficiency of the recoverable magnetic catalyst in Example 11:

[0088] Set up 7 groups of experiments, namely ozone reaction alone, Fe3O4 reacting with ozone and Fe3O4 reacting with oxygen, as well as MgO@Fe3O4@Sep reacting with ozone and MgO@Fe3O4@Sep reacting with oxygen. The catalyst dosage is 0.2 g for all, the concentration of 200 mL of reactive yellow solution is 1000 mg / L, the pH is adjusted to 8, the ozone concentration is set to 40 mg / L, and the ozone concentration in the oxygen group is set to 0 mg / L. The results are as Figure 9As shown, we can see that the degradation effect and adsorption performance of MgO@Fe3O4@Sep (prepared in Example 1) are greatly improved compared to Fe3O4. This is because the prepared MgO@Fe3O4@Sep after modification has a larger specific surface area and increased pore volume compared to the former matrix material, which can greatly improve the adsorption efficiency of the material. According to current mainstream research, there are mainly two views on the reaction mechanism. One view is that ozone molecules directly participate in the oxidation reaction in water, and the other view is that in the presence of a catalyst, ozone in water is catalytically decomposed to generate strongly oxidizing active substances such as hydroxyl radical-like active substances, thereby achieving the oxidative degradation of pollutants. However, the generated free radicals are produced on the catalyst surface and have a very short lifespan, between microseconds and nanoseconds, which easily causes waste of free radicals. Most existing materials have poor degradation effects due to insufficient adsorption performance. Therefore, it is necessary to enhance the adsorption performance of the material so that it can adsorb pollutant molecules and ozone molecules on the catalyst surface simultaneously, enabling hydroxyl radicals (sepiolite, MgO, and Fe3O4 can simultaneously generate hydroxyl radicals from ozone decomposition) to react with pollutants in time during their survival time, thereby improving the catalytic degradation effect of the catalytic material, and proving that the adsorption-catalysis synergistic system is available and has better effects than existing research.

[0089] Degradation performance of the magnetic metal catalyst material for actual wastewater in Application Example 1:

[0090] Weigh 0.4 g of MgO@Fe3O4@Sep prepared in Example 1 and add it to 200 mL of actual wastewater. The actual wastewater is from the influent of the regulation tank in the dyeing and weaving section of an enterprise and is also the effluent of the dyeing and weaving process. Its physical and chemical properties are shown in Table 2. The B / C ratio (BOD5 / COD) before degradation is 0.247 < 0.25, which can be considered that the wastewater is difficult to biodegrade. At the same time, it can be seen that the salt content in the wastewater is relatively large and the composition is relatively complex, especially the Cl - content is very likely to react with ozone or ·OH, which will affect the degradation effect to a certain extent. Adjust the pH to 8 and carry out degradation under the condition of an ozone concentration of 60 mg / L for 40 min. Take out 5 mL of the sample solution every 20 min and measure its ultraviolet-visible absorption spectrum. The results are as Figure 10 shown. The main dye component of the wastewater is reactive red dye. Phenyl azo H-acid type red dye usually shows two absorption peaks with similar intensities near 510 nm and 530 nm, which also conforms to our test results this time. It can be seen from Table 2 that the B / C ratio after 40 min of degradation is 0.347 > 0.3. The biodegradability of the printing and dyeing wastewater is greatly improved after catalytic degradation, and the subsequent wastewater treatment can be achieved through biodegradation. The chroma removal rate reaches 96.7%, and the COD removal rate also reaches 61.7%, proving that the effect of ozone catalysis is very excellent and has very good application prospects.

[0091] Comparative Example 1

[0092] Table 3 compares the best removal rates of different types of catalyst materials and the types of dyes treated under the optimal operating conditions. It can be seen that the MgO@Fe3O4@Sep material prepared by us has very excellent degradation effect, and the recyclable magnetic catalyst prepared by us still has good catalytic performance for high-concentration dye wastewater, and the degradation effect is significantly higher than that of other existing catalysts. The improvement of the catalytic effect can be attributed to the adsorption-catalysis synergistic effect of the material, which improves the adsorption performance of the material and greatly increases the utilization rate of free radicals.

[0093] Table 1

[0094]

[0095] Table 2

[0096]

[0097] Table 3

[0098]

[0099]

[0100] The above are only the preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as a limitation of the present invention, and the protection scope of the present invention should be subject to the scope defined by the claims. For those of ordinary skill in the art of this technology, without departing from the spirit and scope of the present invention, several improvements and refinements can also be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.

Claims

1. A recyclable magnetic catalyst, characterized in that, It includes fibrous sepiolite, as well as magnetite particles and magnesium oxide nanoparticles supported on the sepiolite.

2. The recyclable magnetic catalyst according to claim 1, wherein The particle size of the magnetite particles is 1 - 5 μm, and the particle size of the magnesium oxide nanoparticles is 10 - 50 nm.

3. A method for preparing a recyclable magnetic catalyst as described in claim 1, characterized in that, It includes the following steps: (1) Prepare magnetite particles; (2) Disperse and dissolve sepiolite in water to form solution C, dissolve magnetite particles in water to form particle colloidal suspension D, slowly drip colloidal suspension D into solution C, stir evenly to obtain solution E, then dissolve magnesium chloride hexahydrate in water to prepare solution F, add solution F to solution E, heat and stir to obtain solution G, drip sodium hydroxide solution B into solution G and stir, centrifuge, wash with alcohol, wash with water, and dry the obtained solution, calcine the dried compound, and finally grind and screen the obtained compound to obtain a recyclable magnetic catalyst.

4. The preparation method of the recyclable magnetic catalyst according to claim 3, characterized in that, The method for preparing magnetite particles in step (1) includes: dissolving ferric chloride hexahydrate and ferrous sulfate heptahydrate in an ethylene glycol aqueous solution to prepare solution A, dripping sodium hydroxide aqueous solution B into solution A and stirring, then cooling, washing, drying, and grinding.

5. The preparation method of the recyclable magnetic catalyst according to claim 4, characterized in that, In step (1), when dripping sodium hydroxide aqueous solution B into solution A, adjust the pH to 8 - 10, and the stirring time is 10 - 14 h.

6. The preparation method of the recyclable magnetic catalyst according to claim 3, characterized in that, In step (2), the mass ratio of the sepiolite, magnetite particles, and magnesium chloride hexahydrate is (1 - 1.5):(1.5 - 2.5):(4 - 6).

7. The preparation method of the recyclable magnetic catalyst according to claim 3, wherein, In step (2), the heating and stirring conditions are: heat up to 70 - 90 °C, and the constant temperature stirring time is 0.5 - 1 h.

8. The preparation method of the recyclable magnetic catalyst according to claim 3, characterized in that, In step (2), the calcination conditions are: the calcination temperature in a muffle furnace is 400 - 550 °C, and the calcination time is 4 - 6 h.

9. The preparation method of the recyclable magnetic catalyst according to claim 3, wherein, In step (2), when dripping sodium hydroxide solution B into solution G and stirring, adjust the pH to 8 - 10, and the stirring time is 0.5 - 1 h.

10. Application of a recyclable magnetic catalyst as described in claim 1 in treating printing and dyeing wastewater.